2008
DOI: 10.1248/bpb.31.240
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Effects of St. John's Wort, Harpagophytum Procumbens Extract and Grape Seed Proanthocyanidins Extract in Mice

Abstract: Currently, the consumption of dietary supplement containing botanical products and foods is growing at a remarkable speed, in terms of the promotion of health or prevention and treatment of diseases. The extract from Hypericum perforatum (St. John's wort, SJW) possess clinical efficacy in the therapy of mild to moderate depression. 1,2) The most important constituents of SJW are phloroglucinols such as hyperforin and pseudohyperforin, naphthodianthrones such as hypericin and pseudohypericin, in addition to fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 36 publications
0
42
0
Order By: Relevance
“…These reports confirm and support the hypothesis for the role that SJW has in the modulation of pain perception. This hypothesis has been suggested in a recent paper that indicates the antinociceptive properties of SJW in the mouse formalin test [29].…”
Section: Discussionmentioning
confidence: 74%
“…These reports confirm and support the hypothesis for the role that SJW has in the modulation of pain perception. This hypothesis has been suggested in a recent paper that indicates the antinociceptive properties of SJW in the mouse formalin test [29].…”
Section: Discussionmentioning
confidence: 74%
“…Uchida et al reported that GSPE had a significant antinociceptive effect in mice during the formalin test (Uchida et al, 2008), and Cui et al showed that GSPE plays a protective role against diabetic peripheral neuropathy by ameliorating nerve damage associated with oxidation (Cui et al, 2008). These results suggest that GSPE has an antinociceptive effect.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study reported that an SJW extract was devoid of any antinociceptive effect in the mouse tail-flick test. 35 This discrepancy might be explained by considering that the SJW-induced antinociception is endowed with a bell-shaped trend. The authors looked for an increase in the pain threshold at a concentration about 15 times higher than the effective ones.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our findings, recent experiments performed in the mouse formalin test observed that the SJW antinociception was unaffected by naloxone. 35 It should also be noted that different mechanisms have been proposed for hyperforin, 23 including mechanisms that might be involved in the modulation of the pain threshold. For these reasons, mechanisms other than the opioid cannot be excluded.…”
Section: Binding Of [mentioning
confidence: 99%
See 1 more Smart Citation